Satisfaction with public-private partnership in solid waste management in Ghana - Millicent Abigail Aning-Agyei; Prince George Aning-Agyei; Patrick Osei-Kufuor; Stephen Bugu Kendie (Sustainable Environment)
The study assessed the satisfaction level of stakeholders with Public-Private Partnership (PPP) in Solid Waste Management (SWM) in Ghana. The study was underpinned by the pragmatist paradigm and mixed-methods design. Purposive and stratified random sampling techniques were used to engage 777 respondents for the data. Narrative inquiry, descriptive statistics and ANOVA were used to analyse the data. The study found that even though there was low participation of service users in the contractual arrangement regarding PPP in SWM, the service agreement was highly responsive to their (73%) SWM needs, as they (51.6%) were generally satisfied with the service provided through the agreement. This finding was at variance with the general participation-satisfaction nexus that greater participation leads to stakeholder satisfaction and vice-versa. The implication is that a high level of responsiveness of a service to the needs of stakeholders could sometimes offset the need for greater participation to enhance satisfaction. The result further suggests that the responsiveness-satisfaction nexus is stronger than the participation-satisfaction nexus in the PPP arrangement for SWM in Ghana. The study recommends that PPP arrangements in SWM in Ghana should focus more on adopting innovative ways to deliver services under the agreement to continuously address the immediate needs of service users and sustain their relevance in public service management. It also recommends that Assembly persons should utilise town hall meetings to increase the participation of service users in the contractual and implementation issues regarding PPP in SWM.